Reinforcement of Lime Ash Particles in LDPE - N. Khan,; Z. Ahmed,; M.A. Wasif ,; A. Nafees, (Journal of Basic & Applied Sciences, 2018)
This study presents findings from an experimental investigation on the reinforcement of Lime ash particles (LAP) synthesized from coal fly ash, CaO, and CaSO4 in Low density Polyethylene (LDPE). The Lime ash particles are synthesized by reinforcing 0 to 30 weight percentages of LAP in virgin LDPE using compression moulding. The mechanical properties of composites are studied and results showed that by adding LAP in LDPE as filler the Tensile Strength and Impact Strength of the composite decreases due to poor interfacial bonding between filler particles and LDPE but Hardness and Flexural Properties increases due to improved properties of surface.